What Al-Alusi assumed is attributed to Al-Farra in his interpretation (Ruh Al-Ma’ani) - Zyoud, Hareth (Al-Adab Journal, 2024)
This study addresses the grammatical issues in which Al-Alusi discussed Al-Farra’s views, which initially appeared to contradict the majority, presenting him as having distinct ideas. Al-Alusi introduced Al-Farra as an innovator in grammatical opinions that deviate from proper structure. However, this study demonstrates that, in these matters, Al-Farra was in agreement with the majority of grammarians. Al-Alusi had mistakenly attributed these views to Al-Farra, creating a misperception that led to the erroneous inclusion of Al-Farra’s statements in his work, "Ma’ani Al-Quran," thereby diverting from Al-Alusi’s intended purpose. This study consists of nine issues, each with a specific title. The methodology involves presenting Al-Farra’s ideas as presented by Al-Alusi, then highlighting the misconceptions by comparing them to Al-Farra’s statements in his book "Ma’ani Al-Quran." Additionally, the study explores the attitudes of grammarians regarding these opinions.